Novelties in Glechon (Lamiaceae): Two new species endemic to Rio Grande do Sul (Brazil) - Luz, Laura; de Loreto Bordignon, Sérgio Augusto; Thode, Verônica (Phytotaxa, 2025)
This study describes two new species of Glechon from the state of Rio Grande do Sul, Brazil: G. rupestris and G. villosissima. Comprehensive morphological descriptions, geographical distribution data, and a preliminary assessment of their conservation status are provided. Additionally, photographic documentation of each species is included. A comparative analysis is presented in tables, highlighting and distinguishing morphologically similar species in the region.